Examination of Heavy Metals Lead (Pb) and Cadmium (Cd) in Fishery Products at the Quarantine Center, Quality Control and Safety of Fishery Products, Denpasar, Bali - Dwi Kurniawati; Darmawan Setia Budi (Journal of Marine and Coastal Science, 2023)
Fishery products in Indonesia serve as a vital source of nutrition for the local population and are significant export commodities. However, the presence of chemicals, particularly heavy metals such as lead (Pb) and cadmium (Cd), nearing safety thresholds, has led to export rejections. The aim of this research is to detect heavy metal contaminants in fishery products using Atomic Absorption Spectrophotometry (AAS). This research was conducted at the Fish Quarantine and Inspection Agency Denpasar, Bali. A total of 17 samples of fishery products intended for international export were analyzed. The results of the tests revealed that none of the samples exceeded the allowable threshold for heavy metal contamination.